(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
Blockage effects are a consequence of the interaction between a body and the surrounding boundaries in a constrained flow. For the case of tidal rotors, global blockage (β) is usually defined by the ratio between the swept area of the rotor and the cross-sectional area of a channel. Increasing blockage tends to increase the limits of power extraction (Garrett and Cummins, 2007), as well as thrust on a rotor through an attendant increase of through-rotor mass flow. While these observations have been studied and demonstrated for isotropic blockage effects (e.g., Zilic de Arcos et al. 2020, Bahaj 2007 , Mikkelsen 2002), questions remain regarding the validity of such assumptions for non-isotropic blockage in channels with, e.g., rectangular cross-sections with varying aspect ratios. In this work, we will use CFD simulations to analyze the effect of non-isotropic blockage on a tidal rotor. The study aims to explore these effects using an Actuator-Line representation of an axial-flow rotor, simulated under different blockage ratios (1 %, 5 %, 10%, and 19.7 %), aspect ratios (0.25, 0.5, 0.75, and 1), and tip speed ratios (4, 5, 6, and 7). A total of 64 cases will be considered. For each simulated case, the power, thrust, and spanwise force distributions will be extracted as functions of time, and used to understand the effect of blockage on the performance of tidal rotors. Our preliminary results, in agreement with existing literature, indicate that blockage affects wake development, as seen in Figure , along with power and thrust. These results, for a constant aspect ratio, show power increases up to 26 % for a blockage of 20 %. The bulk of the simulation matrix, including the different aspect ratios, is currently under production and is expected to be ready before the paper submission deadline. References Garrett, C., Cummins, P. (2007). The efficiency of a turbine in a tidal channel. Journal of fluid mechanics, 588, 243-251. Zilic de Arcos, F., Tampier, G., Vogel, C. R. (2020). Numerical analysis of blockage correction methods for tidal turbines. Journal of Ocean Engineering and Marine Energy, 6, 183-197 Bahaj, A. S., Molland, A. F., Chaplin, J. R., Batten, W. M. J. (2007). Power and thrust measurements of marine current turbines under various hydrodynamic flow conditions in a cavitation tunnel and a towing tank. Renewable energy, 32(3), 407-426. Mikkelsen, R., Sørensen, J. N. (2002). Modelling of wind turbine blockage. In 15th IEA symposium on the aerodynamics of wind turbines, FOI Swedish Defence Research Agency.